The Inflammasome Methods and Protocols - De Nardo, Christine M.; Latz, Eicke; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Inflammasomes have a seemingly simple architecture. A sensor molecule of the NLR or PYHIN protein family recruits the common adapter molecule apoptosis-associated speck-like protein containing a CARD (ASC). Even so, inflammasome activation is highly regulated at multiple steps and precise details of how inflammasomes are activated at the molecular level remain largely unknown. In The Inflammasome: Methods and Protocols, expert researchers in the field detail methods and protocols to study multiple aspects of inflammasome function. These methods include the generation of inflammasome stimuli, perturbance of cellular homeostasis, assessment of ASC speck formation, monitoring of caspase-1 activity and processing, activation of IL-1β cytokines, and analysis of inflammasome assembly. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.
Assessing b-amyloid-induced NLRP3 Inflammasome Activation in Primary Microglia -- Activating the NLRP3 Inflammasome using the Amyloidogenic Peptide IAPP -- Assessment and Quantification of Crystal-induced Lysosomal Damage -- Assessment of Inflammasome Activation in Primary Human Immune Cells -- NLRP3 Inflammasome Activation and Cytotoxicity Induced by particulate Adjuvants -- Measuring Inflammasome Activation in Response to Bacterial Infection -- Detection of Pyroptosis by Measuring Released Lactate Dehydrogenase Activity -- ASC Speck Formation as a Read-out for Inflammasome Activation -- Immunoblotting for Active Caspase-1 --  Inflammasome Activation and Inhibition in Primary Murine Bone Marrow-Derived Cells, and Assays for IL-1α, IL-1β and Caspase-1 -- Reconstituting the NLRP1 Inflammasome in vitro -- Assessing ATP Binding and Hydrolysis by NLR Proteins -- Blue Native Polyacrylamide Gel Electrophoresis to Monitor Inflammasome Assembly and Composition -- Analysis of Microbiota Alterations in Inflammasome-deficient Mice -- Quantification of Adipose Tissue Leukocytosis in Obesity -- In vivo Evaluation of Neutrophil Recruitment in Response to Sterile Particulates.
Keywords: Immunology; Cytokines; Growth factors; Immunology; Cytokines and Growth Factors